Medicinal plants used in Gabon for prophylaxis and treatment against COVID-19-related symptoms: an ethnobotanical survey - Boukandou Mounanga, Marlaine Michel; Mezui, Annais; Mewono, Ludovic; Mogangué, Jean Bertrand; Aboughe Angone, Sophie (Frontiers in Pharmacology, 2024)
Gabon has faced COVID-19 with more than 49,000 individuals tested positive and 307 recorded fatalities since the first reported case in 2020. The popular hypothesis sounds that, the low rate of cases and deaths in the country was attributed to the use of medicinal plants in prevention and treatment. This study aimed to document plants used for remedial and preventive therapies by the Gabonese population during the COVID-19 pandemic and to pinpoint specific potential plant species that merit further investigation An ethnobotanical survey involving 97 participants was conducted in Libreville. Traditional healers and medicinal plant vendors were interviewed orally using a semi-structured questionnaire sheet, while the general population responded to an online questionnaire format. Various quantitative indexes were calculated from the collected data and included the relative frequency of citation (RFC), Use Value (UV), Informant Consensus Factor (ICF), Relative Importance (RI), and Popular Therapeutic Use Value (POPUT). ANOVA One-way and Independent Samples t-Test were used for statistical analyses. p-values ≤ 0.05 were considered significant. Results: The survey identified 63 plant species belonging to 35 families. Prevalent symptoms treated included fever (18%), cough (16%), fatigue (13%), and cold (12%). The demographic data highlighted that 52.58% of males (p>0.94) aged 31-44 years were enrolled in the survey, in which, the most represented at 48.45% (p<0.0001) and 74.73% (p<0.99) of informants had university level. In addition, the results indicated that a total of 66% of the informants used medicinal plants for prophylaxis (34%), for both prevention and treatment (26%), exclusively for treatment (3%), and only for prevention (3%) while suffering from COVID-19, against 34% of the participants which did not use plants for prevention or treatment. Annickia chlorantha, Citrus sp., Alstonia congensis, Zingiber officinale, and Carica papaya emerged as the most commonly cited plants with the highest RFC (0.15 to 0.26), UV (0.47 to 0.75) and RI (35.72 to 45.46) values. Most of these plants were used either individually or in combination with others. The survey reinforces the use of traditional medicine as a method to alleviate COVID-19 symptoms, thereby advocating for the utilization of medicinal plants in managing coronavirus infections.